2022
DOI: 10.3390/app12094290
|View full text |Cite
|
Sign up to set email alerts
|

Grain Boundary—A Route to Enhance Electrocatalytic Activity for Hydrogen Evolution Reaction

Abstract: The electrocatalytic hydrogen evolution reaction (HER) of a given metal catalyst is intrinsically related to its electronic structure, which is difficult to alter for further improvement. Recently, it was discovered that the density of grain boundaries (GBs) is mechanistically of great importance for catalytic activity, implying that GBs are quantitatively correlated with the active sites in the HER. Here, by modeling the atomistic structure of GBs on a Au(110) surface, we find that HER performance is greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…These TOFs were orders of magnitude higher than previously reported TOFs for tungsten carbides reported in the literature (Table ). This can be attributed to the high density of grain boundaries in the WC films. The disordered atomic arrangement at the grain boundaries causes symmetry breaking, altering of the electronic structure, and an increase in the d z 2 orbital energy level of W. ,, In hydrogen evolution, the adsorption strength of H atoms on the W surface (σ bond between H 1s and W d z 2 ) determines the electrocatalytic activity based on Sabatier’s principle. The WC samples with a high density of GBs and more efficient active sites (optimized Δ G H* ) led to the high intrinsic activity (based on TOF).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These TOFs were orders of magnitude higher than previously reported TOFs for tungsten carbides reported in the literature (Table ). This can be attributed to the high density of grain boundaries in the WC films. The disordered atomic arrangement at the grain boundaries causes symmetry breaking, altering of the electronic structure, and an increase in the d z 2 orbital energy level of W. ,, In hydrogen evolution, the adsorption strength of H atoms on the W surface (σ bond between H 1s and W d z 2 ) determines the electrocatalytic activity based on Sabatier’s principle. The WC samples with a high density of GBs and more efficient active sites (optimized Δ G H* ) led to the high intrinsic activity (based on TOF).…”
Section: Resultsmentioning
confidence: 99%
“…This can be attributed to the high density of grain boundaries in the WC films. 43−46 The disordered atomic arrangement at the grain boundaries causes symmetry breaking, altering of the electronic structure, and an increase in the d z 2 orbital energy level of W. 43,47,48 In hydrogen evolution, the adsorption strength of H atoms on the W surface (σ bond between H 1s and W d z…”
Section: Electrocatalytic Her Performancementioning
confidence: 99%
“…The TEM bright-field image shows a contrast sensitive to the grain orientations and therefore reveals that the synthesized Ni thin films are nanocrystalline with an estimated mean grain size of ~9 nm. This small grain size and, therefore, high density of grain boundaries (GBs) has already been found to potentially have a positive influence on the catalytic activity towards HER [ 36 , 37 ]. It was shown in a combined DFT and experimental study by Jiang et al that the GBs efficiently affect the activity of Au catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown in a combined DFT and experimental study by Jiang et al that the GBs efficiently affect the activity of Au catalysts. As a consequence, it is concluded that a high density of GBs can be traced to an increased ability to adsorb hydrogen and stabilize H* during the reaction steps [ 37 ]. The accompanying selected area electron diffraction (SAED) pattern and the corresponding profile obtained by azimuthal integration [ 38 ] confirm the polycrystalline fcc structure of the sputter-deposited film ( Figure 1 a).…”
Section: Resultsmentioning
confidence: 99%
“…found that HER activity is inherently correlated with the density of the GBs in Au NPs, where active sites bind H 2 more strongly [3]. Their finding holds promise for enhancing the catalyst's HER performance.…”
Section: Application Of Energy Saving and Low-carbon Technologies In ...mentioning
confidence: 89%